ACSL3 promotes intratumoral steroidogenesis in prostate cancer cells. Issue 10 (10th September 2017) - Migita, Toshiro; Takayama, Ken‐ichi; Urano, Tomohiko; Obinata, Daisuke; Ikeda, Kazutaka; Soga, Tomoyoshi; Takahashi, Satoru; Inoue, Satoshi
Abstract : Long‐chain acyl‐coenzyme A (CoA) synthetase 3 ( ACSL3 ) is an androgen‐responsive gene involved in the generation of fatty acyl‐CoA esters. ACSL3 is expressed in both androgen‐sensitive and castration‐resistant prostate cancer (CRPC). However, its role in prostate cancer remains elusive. We overexpressed ACSL3 in androgen‐dependent LNCaP cells and examined the downstream effectors of ACSL3. Furthermore, we examined the role of ACSL3 in the androgen metabolism of prostate cancer. ACSL3 overexpression led to upregulation of several genes such as aldo‐keto reductase 1C3 ( AKR1C3 ) involved in steroidogenesis, which utilizes adrenal androgen dehydroepiandrosterone sulfate (DHEAS) as substrate, and downregulated androgen‐inactivating enzyme UDP‐glucuronosyltransferase 2 ( UGT2B ). Exposure to DHEAS significantly increased testosterone levels and cell proliferative response in ACSL3‐overexpressing cells when compared to that in control cells. A public database showed that ACSL3 level was higher in CRPC than in hormone‐sensitive prostate cancer. CRPC cells showed an increased expression of ACSL3 and an expression pattern of AKR1C3 and UGT2B similar to ACSL3‐overexpressing cells. DHEAS stimulation significantly promoted the proliferation of CRPC cells when compared to that of LNCaP cells. These findings suggest that ACSL3 contributes to the growth of CRPC through intratumoral steroidogenesis (i.e. promoting androgen synthesis from DHEAS and preventing the catabolism of active androgens). Abstract : Long‐chain acyl‐coenzyme A synthetase 3 (ACSL3) expression is increased in both hormone sensitive and refractory prostate cancer. We found that ACSL3 contributes to intratumoral steroidogenesis by modulating steroidogenic genes, thereby promoting the growth of hormone refractory prostate cancer.